2014
DOI: 10.1080/00140139.2014.957733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of work experience on fatigue-induced biomechanical changes during repetitive asymmetric lifts/lowers

Abstract: Repetitive lifting/lowering is associated with an increased risk of work-related low back disorders (WRLBDs), and fatigue may exacerbate such risk. Work methods used by experienced workers are potential models for developing worker training to reduce WRLBDs, though whether experience modifies the effects of fatigue on WRLBD risk is largely unknown. Here, six novices and six experienced workers completed 185 cycles of repetitive, asymmetric lifts/lowers. Physical demands, whole-body balance and torso movement s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…f) Increased forward bending, also described by Mehta et al (2014); g) Head slightly bending forward; h) Neck bending sideways; i) Decrease in body stability; j) Changing support leg (some volunteers started to feel numb legs); Evaluation of physical fatigue based on motion analysis in manual handling of loads Bernardo et al k) Stretching body and spine; l) Holding load closer to the chest during elevation in the final stages of the experiment, resulting in a less fluid movement. This shows volunteers adapted to compensate fatigued muscles, which was also concluded by McDonald et al (2016), Lee et al (2014) and Gates et al (2011); m) Increased difficulty to follow metronome rhythm;…”
Section: Posture and Behavioral Changes Recorded On Camera And Symptomentioning
confidence: 54%
See 1 more Smart Citation
“…f) Increased forward bending, also described by Mehta et al (2014); g) Head slightly bending forward; h) Neck bending sideways; i) Decrease in body stability; j) Changing support leg (some volunteers started to feel numb legs); Evaluation of physical fatigue based on motion analysis in manual handling of loads Bernardo et al k) Stretching body and spine; l) Holding load closer to the chest during elevation in the final stages of the experiment, resulting in a less fluid movement. This shows volunteers adapted to compensate fatigued muscles, which was also concluded by McDonald et al (2016), Lee et al (2014) and Gates et al (2011); m) Increased difficulty to follow metronome rhythm;…”
Section: Posture and Behavioral Changes Recorded On Camera And Symptomentioning
confidence: 54%
“…Muscular and kinematic adaptations occur to reduce the load on the fatigued muscles (McDonald et al, 2016). Other studies concluded that fatigue-induced changes in movement strategies (Lee et al, 2014) and subjects altered their kinematic patterns significantly in response to muscle fatigue (Gates et al, 2011).…”
Section: Posture and Behavioral Changes Recorded On Camera And Symptomentioning
confidence: 99%
“…4 Repetitive movements during work or activities of daily living can result in injury, especially of the low back. 5 Variation in movements, posture or muscle activity has been suggested as an effective strategy to minimise the load associated with repetitive movements and hence may prevent or delay any potential musculoskeletal injury. 6 Motor variability is an important feature to consider when performing repetitive movement, and in asymptomatic people functional tasks are typically performed with variable motor patterns.…”
Section: Introductionmentioning
confidence: 99%